ASPEK MORAL DALAM CERPEN JIMAT MALOWOPATI KARYA TEGSA TEGUH SATRIYO: TINJAUAN SEMIOTIK - Rahma Mardiana Kurniasih (Universitas Sebelas Maret, 2023)
This study aims to examine moral values based on semiotic studies by applying Roland Barthes' theory. This study uses an approach as well as a method, namely descriptive qualitative. In addition, the research data is the text of a short story entitled Jimat Malowopati by Tegsa Teguh Striyo which is one of the short stories from a collection of short stories titled Covid-19 with the title Short story #ProsaDiRumahAja owned by Putu Fajar Arcana. The results of this study found that there were three types of moral values in the short story Jimat Malowopati by Tegsa Teguh Satriyo, namely social moral values, religious moral values wrapped in culture, and individual cultural values. This moral value is dominantly represented through two characters in the short story, namely Mbah Girut and Kang Subur. Through this research, the researcher hopes that there will be further studies that can improve this research.